Pengaruh Pembelajaran Campuran Terhadap Pencapaian Mahasiswa - Silvi Maulina Sagita; Putri Nurrahman (Global Synthesis in Education Journal, 2023)
This study examines the effect of blended learning on student learning achievement. Blended learning is a mixture of online and face-to-face or traditional learning. The purpose of this research is to find out the positive or negative effect of blended learning. The method used is descriptive quantitative. Data was obtained from distributing questionnaires to selected respondents. The data that has been collected and calculated shows that there are more positive effects of blended learning where one of them is the achievement of better student academic scores. However, it is crucial to note a divergence in student preferences revealed in the study. Despite the positive academic outcomes, some students express a preference for face-to-face learning over online components within the blended learning model. While the academic achievements indicate a positive trend, the acknowledgment of student preferences introduces a layer of complexity. The recognition that some students favor traditional face-to-face instruction suggests that the success of blended learning may vary among individuals. the study underscores the need for further research to delve into the potential negative effects of blended learning. By addressing this aspect, educators and policymakers can gain a more comprehensive understanding of the dynamics involved in implementing blended learning approaches, facilitating informed decision-making to optimize the learning experience for diverse student populations. Further research is also needed to analyze the negative effect of blended learning